Humoral vaccine responses following Chimeric Antigen Receptor T-cell therapy for hematological malignancies - Sigrun Einarsdottir; Stephanie Lobaugh; Danny Luan; Marina Gomez-Llobell; Padmapriya Subramanian; Sean Devlin; David Chung; Parastoo B. Dahi; Lorenzo Falchi; Sergio Giralt; Heather Landau; Alexander M. Lesokhin; et al. (Blood Cancer Journal)
Abstract This single-center, retrospective study analyzed vaccine responses in patients who received post-Chimeric Antigen Receptor (CAR) T-cell therapy vaccination between 2018 and 2024. Vaccinations were administered according to EBMT/CIBMTR recommendations and pathogen-specific IgG responses to 12 vaccine-preventable infections were assessed. Seroprotection was defined by established cut-offs or a significant fold increase in titers. A total of 73 patients that had not received intravenous immunoglobulins within the eight weeks prior to pre- or post titer were included. The median time to vaccination initiation was 13 months (range 6–66) post-CAR T. Pre and post-vaccination titers were available for 49 patients. Pre-vaccination seroprotection was high (> 85%) for tetanus and poliovirus. Among patients not seroprotected prior to vaccination, vaccine response rates were high for tetanus and polio (100%), moderate for diphtheria (75%) and haemophilus influenzae type b (62%), and lower for pertussis (48%), hepatitis A (43%), hepatitis B (44%), and pneumococcal disease (33%). CD19 CAR T recipients had higher pre-vaccination seroprotection rates than BCMA recipients, but vaccine responses did not differ significantly between groups. Pre-vaccination IgA levels were significantly associated with vaccine response, and absolute B-cell counts trended higher among responders (p = 0.054). Our findings highlight the importance of immune reconstitution in vaccine responses post-CAR T.